The common origin for diverse autoimmune diseases - Anaya, Juan-Manuel (Henry Stewart Talks, 2007)
Autoimmune diseases, The autoimmune kaleidoscope, Clinical evidence, Familial autoimmune diseases, Physiopathology, Autoimmune diseases are heterogeneous and multifactorial, How important is the genetic predisposition on susceptibility to autoimmune diseases?
Archived at 2018/10/25